European Central Bank accountability: How the monetary dialogue could be improved - Grégory Claeys; Mark Hallerberg; Olga Tschekassin (Bruegel, 2014)
According to the European Union Treaties, the European Central Bank (ECB) is accountable to the European Parliament. In practice, this accountability takes mainly the form of a quarterly Monetary Dialogue between the president of the ECB and the European Parliament Economic and Monetary Affairs committee. We assess the impact of the Monetary Dialogue. We describe the ECB's accountability practices, compare them to those of other major central banks and provide an assessment of the dialogue in the last five years. The Monetary Dialogue could be improved and we make recommendations on this. We also consider what role the Monetary Dialogue could play in the current context of the ECB's evolving role. We discuss in particular forward guidance and quantitative easing. We review the main features and the way in which those policies have been implemented by other central banks. We then suggest the appropriate role for the Monetary Dialogue in relation to each of those policies. We conclude with some observations on the function of the Monetary Dialogue after the establishment of a banking union in Europe
Keywords: 330; Zentralbank; Eurozone; Zentralbankunabhängigkeit